ICS Effectiveness, Application AIS, HRC on Good Governance and Impact Quality FS - MARZUKI, Ismail; HIDAYAH, Nurul (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to determine the effect of the effectiveness of the internal control system, the application of accounting information systems, and the competence of human resources on the implementation of good governance and its impact on the quality of regional financial statements. This research was conducted at the Regional Organization (OPD) in South Tangerang City using the purposive sampling method and conducted a survey of 30 OPD as a research sample. Data collection was carried out by distributing questionnaires to 100 respondents. The data analysis method uses descriptive statistical analysis using SEM PLS as an analytical tool in this study. The results showed that: the effectiveness of the internal control system has a positive and significant effect on good governance, the application of the accounting information system does not have a significant effect on good governance, Human resource competence does not have a significant effect on good governance, the effectiveness of internal control does not have a significant effect on the quality of financial statements, the establishment of accounting information systems has no significant effect on financial statements, human resource competence has no significant effect on financial statements, and good governance has a positive and significant impact on the quality of financial statements.